2017
DOI: 10.1016/j.ijpe.2017.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Inventories and the concentration of suppliers and customers: Evidence from the Chinese manufacturing sector

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International licence Newcastle University ePrints -eprint.ncl.ac.uk Casalin F, Pang G, Maioli S, Cao T. Inventories and the concentration of suppliers and customers: Evidence from the Chinese manufacturing sector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 45 publications
0
42
0
Order By: Relevance
“…6 We first obtain 152 firms that adopted GRI for at least three continuous years during the period 2008-2016 from the CSMAR database. In the process, we exclude financial services and real estate companies because their data are very different from that of other firms (H. Kang & Liu, 2014) and those issuing B shares (subscribed, bought, and sold in foreign currencies) or H shares (denominated in the Hong Kong dollar) (Casalin, Pang, Maioli, & Cao, 2017). There are 122 GRI-reporting firms remained.…”
Section: Event Study Methodsmentioning
confidence: 99%
“…6 We first obtain 152 firms that adopted GRI for at least three continuous years during the period 2008-2016 from the CSMAR database. In the process, we exclude financial services and real estate companies because their data are very different from that of other firms (H. Kang & Liu, 2014) and those issuing B shares (subscribed, bought, and sold in foreign currencies) or H shares (denominated in the Hong Kong dollar) (Casalin, Pang, Maioli, & Cao, 2017). There are 122 GRI-reporting firms remained.…”
Section: Event Study Methodsmentioning
confidence: 99%
“…As summarized in Table 1, existing research mainly investigates the effect of SPC on operational outcomes and firm performance. For example, high SPC has been found to reduce product recalls (Steven et al, 2014), decrease the insourcing ratio in plural sourcing (Sako et al, 2016), enable firms to hold fewer inventories (Casalin et al, 2017), increase firms' cash holdings (Zhang et al, 2020), and improve financial performance (Elking et al, 2017). Besides, Schwieterman et al (2018) investigated the effect of SPC on firm credit risk and revealed that SPC is not significant to credit ratings.…”
Section: A Literature Review Of Supplier Portfolio Concentrationmentioning
confidence: 99%
“…To fully obtain the cooperation and competition status of the supplier relationship strategy, the measurement index of the supplier relationship strategy requires reflecting not only the closeness of the relationship between enterprises and suppliers but also their bargaining advantages. This study refers to the existing literature and applies supplier concentration as one of the indicators to measure the supplier relationship strategy ( 16 , 17 , 59 , 60 ). For another dimension of supplier relations, considering the work of Wang and Wang ( 61 ), supplier financing that is the net occupation of enterprises, to supplier financing, is selected.…”
Section: Sample Selection and Datamentioning
confidence: 99%